Downward Social Mobility and Major Depressive Episodes Among Latino and Asian-American Immigrants to the United States - Nicklett, Emily J. (Oxford University Press, 2009)
The authors analyzed the association between downward social mobility in subjective social status among 3,056 immigrants to the United States and the odds of a major depressive episode. Using data from the National Latino and Asian American Study (2002–2003), the authors examined downward mobility by comparing immigrants’ subjective social status in their country of origin with their subjective social status in the United States. The dependent variable was the occurrence of a past-year episode of major depression defined according to Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, criteria. Logistic regression models were used to control for a variety of sociodemographic and immigration-related characteristics. Analyses suggested that a loss of at least 3 steps in subjective social status is associated with increased risk of a depressive episode (odds ratio = 3.0, 95% confidence interval: 1.3, 6.6). Other factors independently associated with greater odds of depression included Latino ethnicity, female sex, having resided for a longer time in the United States, and being a US citizen. The findings suggest that immigrants who experience downward social mobility are at elevated risk of major depression. Policies or interventions focused only on immigrants of low social status may miss another group at risk: those who experience downward mobility from a higher social status.